Herencia cultural y colonialidad del poder un enfoque desde Mamita Yunai - Martínez, María (2009)
This paper shows that Mamita Yunai, as heritage of the Costa Rican culture, presents interesting features from the perspective of three actors of the national identity: the Costa Rican "Creole," "black" and "Indian". Following the Theory of Decolonial Thought, we proposed a reading of the novel understood as a reflection of the cultural heritage of Costa Rica in regarding the construction of identities.